PENGARUH MOTIVASI TERHADAP DISIPLIN PEGAWAI BALAI BESAR KONSERVASI SUMBER DAYA ALAM RIAU - Ansori, Putra Budi; Suratman, Suratman (Sekolah Tinggi Ilmu Ekonomi Riau, 2021)
This research was conducted in the research conducted at the great hall of conservation of Riau's natural resources in 2020. The purpose of research is know whether Work-Disipline significant of the performance of an employee in the great hall of conservation of Riau's natural resources. Because motivation of the creation was make civil servants that they employ zealous in perform his her job so that have sent down blessed sheer terror of being conscious to obey regulation to achieve organizational goals .Population in this research is population in research it is a whole an employee of the great hall of conservation of Riau's natural resources of 126 employees in 2019 with a sample of 56 employees with a sampling method based on Insidental sampling. Based on the values t obtained t count of 6,589 while value t table was in 2,00488 which means t count = 6,589 > 2,00488, then H0 turned down and Ha received is the Work-Motivation of the discipline of employees of the great hall of conservation of Riau's natural resources. The Work-Motivation of the discipline of employees of the great hall of conservation of Riau's natural resources of 44,6 % and 55,4 % influenced by the other factors that are not pursuing in this research .The research showed that motivation work have had a positive impact and significant impact on the awareness of discipline of the great hall of conservation of Riau's natural resources. With the regression equation is linear simple as follows: Y = 13,038 + 0,712 X. So this research to strengthen previous studies.